Konvergáló Erdély-percepciók : interetnikus értelmiségi párbeszéd a térség kontextusában - Miklósné Zakar, Andrea (Közép-Európai Közlemények, 2012)
It is very important to emphasize the relevance of interethnic dialogues of intellectuals which have taken place in the context of Transylvania, because the future of this region cannot be imagined without the consensus of all the nationalities living there together. This study analyses the Romanian and Hungarian disputes published in the periodical “Altera” (issued by the intercultural centre Liga Pro Europa) and in the monthly “Provincia” (issued between 2000 and 2002). The analysis of the texts aims to present this dialogue as a special form of regionalism, focusing on Transylvania, as a special region. The discourses focus on the following main ideas: Transylvania as a special multicultural are; the importance of transethnic identity; the comparison of regionalisation models which give free rein to different forms of autonomies; criticism of Romania’s decentralisation process; the Memorandum in 2001 – which seems to be the result of the consensus of intellectuals involved in the analysed dialogue.